The definitive guide to modernizing applications on Google Cloud : the what, why, and how of application modernization on Google Cloud /: the what, why, and how of application modernization on Google Cloud. (2022) - Sangapu, Steve; Panyam, Dheeraj; Marston, Jason
No abstract available